Analisis Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII SMP Negeri 6 Tambun Selatan Pada Materi Sistem Persamaan Linier Dua Variabel (SPLDV): Analysis of Mathematical Problem Solving Ability of Class VIII Students of SMP Negeri 6 Tambun Selatan on the Material of Two-Variable Linear Equation System (SPLDV) - Oktaviani, Rhisma Putri (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to describe the mathematical problem solving ability of class VIII students of SMP Negeri 6 Tambun Selatan on the material of Two-Variable Linear Equation System (SPLDV). Using descriptive qualitative approach, the research was conducted on 38 students with purposive sampling. Data were collected through problem solving tests and semi-structured interviews. The results showed that students' mathematical problem solving skills were low, with 78.95% of students in the low criteria, 13.16% medium, and only 7.89% high. Based on Polya's indicators, the majority of students were only able to describe the problem and develop a solution plan, while having difficulty at the stage of implementing the plan and re-examining the results. High ability students were able to fulfill all indicators, medium ability students were only able to fulfill the first two indicators, while low ability students had difficulty in almost all indicators. Students' main obstacles include difficulty translating story problems into mathematical models, lack of understanding of concepts, and inability to check results. A more effective learning approach is needed to improve students' mathematical problem solving skills.